Identifying clinical phenotypes for hospitalized patients with chronic obstructive pulmonary disease acute exacerbation - Mayar Mamdoh; Mohamed A.H. El Nady; Hebatallah H. Assal; Gihan Saad; Amira I.A. Eldin; May S. Soliman; Amani A. Elkholy; Sara E.E. Haddad; Noha S. Soliman; Gehan Hamdy (Journal of the Arab Society for Medical Research)
Background/aim Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is common and has clinical consequences, such as a decline in quality of life, reduction in lung functions, hospitalization, and death. This study aims to assess the clinical phenotyping of hospitalized patients with AECOPD, and the correlation between the phenotype of Chronic Obstructive Pulmonary Disease (COPD) exacerbation and clinical outcome. Patients and methods This is a prospective cross-sectional study which included thirty- nine patients from the Chest diseases department, Faculty of Medicine, Cairo University. Each patient was subjected to full history taking, clinical examination, plain chest radiography, bacterial culture, viral polymerase chain reaction, modified medical research council dyspnea scale, and COPD assessment test. Results Most of our patients were males (92.3%), mean age was 65.33±9.73 years, 92% of the study populations were smokers and the mean BMI was 25.94±5.04 kg/m2. Four phenotypes were identified as bacterial, viral, co-infection, and noninfectious. Regarding the clinical outcome, the viral phenotype had the highest ICU admission rate (58.3%), while the co-infection phenotype had the highest mean duration of hospital stay (18.13±16.8 days), and in-hospital mortality of 37.5%. Conclusion Clinically important differences in outcomes suggest that a phenotyping strategy based on etiologies can enhance AECOPD management.